Isolation and characterisation of allelic variations in FT/TFL1 gene homologs among various cultivars and ems-derived m2 mutants of eggplant (solanum melongena) - Ranjita A/P Subramaniam (2023)
FT/TFL1 gene homologs are one of the key determinants in flowering regulation, seed dormancy and germination. Despite their utilization for crop improvements in various species, they have not been identified and characterized in eggplant (S. melongena). Moreover, since the allelic diversities of the gene family represent important resources for crop improvement, the identification of diverse alleles can be facilitated by different varietal cultivars and EMS-derived mutants. Therefore, the project aimed to identify FT/TFL1 genes in eggplant using in-silico genome mining with three genome assemblies i.e. Sme_r2.5.1, S. melongena-HQ and ‘67/3’. Subsequently, the deduced protein sequences were characterized. The presence of these genes was validated in four economically important cultivars Surya, EP-47 Annamalai, Pant Samrat and Arka Nidhi through Pacbio RSII amplicon sequencing, using plants grown from seeds obtained from the World Vegetable Centre. Distribution of allelic variations were identified among them. Meanwhile, initial seeds from seven cultivars were used to establish M1 mutant libraries with 0.7% EMS. In M2 generation, mutant libraries were narrowed to Surya, EP-47 Annamalai, Pant Samrat, and Arka Nidhi, with gene analysis conducted through Pacbio RSII sequencing. Morphological variations were also recorded. The results unravelled the presence of 12 FT/TFL1 gene homologs in eggplant, with evidence of FT-like gene diversifications, suggesting differential responses to various environmental cues. The amplicon sequencing and variant phasing uncovered the presence of two alleles in certain genes (SmCEN-1, SmCEN-2, SmMFT-1, and SmMFT-2). An examination of SmMFT-2 alleles across domesticated cultivars and the related wild species, S. incanum, indicated that the alternative allele of S. incanum was present in some Pant Samrat cultivar members but lacking in most other cultivars. This variation could contribute to the discrepancies in seed traits between wild and domesticated eggplants. Furthermore, EMS-mediated mutagenesis led to the discovery of a mutation in the predicted 5′UTR region which needs further verifications on their influence on the underlying traits. The mutagenesis also led to the emergence of various desirable traits. Taken together, the study provided fundamental details about the FT/TFL1 gene family with identification of valuable allelic diversities that can lay the foundation for future functional validations and their downstream applications in alignment to the crop’s improvement programs.